Analisis penerapan supply chain management pada industri pengolahan emas skala kecil (Studi Kasus: CV. Pohuwato Jaya Abadi) - Rasyid, Abdul; Tantu, Dewirna (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
CV. Pohuwato Jaya Abadi is a business engaged in the mining industry in Gorontalo. During its supply chain activities, this MSME has experienced problems in the production procurement process and delivery that is not on time. The procurement process of MSMEs has experienced shortages in the supply of raw materials so that it affects the production process in the form of not achieving production targets and late delivery of products. In an effort to solve the problem, MSME supply chain performance measurement is carried out using the SCOR and AHP methods which aim to identify supply chain performance by knowing what indicators are used and providing suggestions for improvement. The results showed that there were 16 performance indicators selected. Based on the results of data processing, it shows 8 performance indicators that need to be improved.